Pemberdayaan Masyarakat Melalui Pemanfaataan Berenuk di Desa Wisata Kubang Baros Serang Banten - Umam, Chotibul; Indriana, Ina; Nurhayati, Enok (Jurnal Ilmiah Pangabdhi, 2024)
Kubang Baros Tourism Village, located in Serang district, Banten province, has natural, cultural and Creative Economy tourist attractions. The existence of a tourist village requires creativity and innovation from the community to create a creative economy based on local wisdom. One of the creative economies based on local wisdom is the use of Berenuk fruit (Crescentia cujete L.), which is made into Kriya (handicrafts) and Maja fruit herbal medicine. This can open up business opportunities to improve the economic welfare of local communities. Identification of partner problems shows that a) business management, production capacity of Maja fruit crafts and herbal medicine is still low b) the appearance of the logo/brand is not attractive c) the marketing used is conventional. Solutions offered to partners: a) designing a more attractive logo/brand b) community service program providing marketing training for maja fruit crafts and herbal medicine through e-commerce. The output target of the service program is that "Sinar Harapan" craftsmen partners become economically independent communities. The community service program is implemented for 3 (three) months for partners, detailed output targets are as follows: a) Increasing the capacity of Maja handicraft and fruit herbal medicine products, b) increasing knowledge regarding product marketing strategies. The success indicator of this program is an increase knowledge and skills regarding product marketing strategies, namely e-commerce, apart from conventional sales; The work procedures in this program include: Socialization Stage, Training/mentoring Stage and Evaluation Stage.